Hepatitis C virus NS4B protein targets STING and abrogates RIG‐I–mediated type I interferon‐dependent innate immunity123. Issue 1 (7th January 2013) - Nitta, Sayuri; Sakamoto, Naoya; Nakagawa, Mina; Kakinuma, Sei; Mishima, Kako; Kusano‐Kitazume, Akiko; Kiyohashi, Kei; Murakawa, Miyako; Nishimura‐Sakurai, Yuki; Azuma, Seishin; Tasaka‐Fujita, Megumi; Asahina, Yasuhiro; et al.
Abstract Hepatitis C virus (HCV) infection blocks cellular interferon (IFN)‐mediated antiviral signaling through cleavage of Cardif by HCV‐NS3/4A serine protease. Like NS3/4A, NS4B protein strongly blocks IFN‐β production signaling mediated by retinoic acid–inducible gene I (RIG‐I); however, the underlying molecular mechanisms are not well understood. Recently, the stimulator of interferon genes (STING) was identified as an activator of RIG‐I signaling. STING possesses a structural homology domain with flaviviral NS4B, which suggests a direct protein‐protein interaction. In the present study, we investigated the molecular mechanisms by which NS4B targets RIG‐I–induced and STING‐mediated IFN‐β production signaling. IFN‐β promoter reporter assay showed that IFN‐β promoter activation induced by RIG‐I or Cardif was significantly suppressed by both NS4B and NS3/4A, whereas STING‐induced IFN‐β activation was suppressed by NS4B but not by NS3/4A, suggesting that NS4B had a distinct point of interaction. Immunostaining showed that STING colocalized with NS4B in the endoplasmic reticulum. Immunoprecipitation and bimolecular fluorescence complementation (BiFC) assays demonstrated that NS4B specifically bound STING. Intriguingly, NS4B expression blocked the protein interaction between STING and Cardif, which is required for robust IFN‐β activation. NS4B truncation assays showed that its N terminus, containing the STING homology domain, was necessary for the suppression of IFN‐β promoter activation. NS4B suppressed residual IFN‐β activation by an NS3/4A‐cleaved Cardif (Cardif1‐508), suggesting that NS3/4A and NS4B may cooperate in the blockade of IFN‐β production. Conclusion: NS4B suppresses RIG‐I–mediated IFN‐β production signaling through a direct protein interaction with STING. Disruption of that interaction may restore cellular antiviral responses and may constitute a novel therapeutic strategy for the eradication of HCV. (HEPATOLOGY 2013)